Thyrotoxicosis and Heart Failure - a Case Report - Alexandru-George COTOBAN; Vlad Damian VINTILA; Cristina CONSTANTINESCU; Antonia NICA; Berenice Maria Claudia SURAN; Dragos VINEREANU (Sciendo, 2021)
Introduction Heart failure (HF) with reduced ejection fraction is a complex condition requiring comprehensive diagnostic workup and management. Case presentation A 62-year-old male presented with resting HF and multiple syncopes. Medical history: former smoker, type 2 diabetes, advanced peripheral artery disease. Physical examination: congestive HF, obesity, discrete exophthalmia, grade 1 goitre, BP 110/70 mmHg, HR: 180 bpm. ECG: atrial fibrillation (AF), 180 bpm, RBBB, ST depression in anterolateral leads. CXR: pulmonary congestion, right pleural effusion. Blood analysis: D-dimer >5ng/ml, NTproBNP 12.900 pg/ml, hsTnI 550 ng/L, low TSH, fT3, fT4 4xULN. Cardiac echo: LVEF 20%, diffuse hypokinesis. HF symptom improvement with decongestion and rate control medication. Methimazole started on day 3. Intermittent conversion to sinus rhythm (SR) on day 7. ECG Holter (day 8-9): alternating moderate/high-rate AF and SR, 5-8 second sinus pauses and 1 syncope. LVEF 35% (day 9). Dual-chamber pacemaker implanted on day 10. Discharged on day 18. 2-months follow-up: LVEF 45%, NTproBNP 1.100 pg/ml, SR, HR 65-70 bpm, NYHA I HF. Conclusion Cardiac and non cardiac aggravating factors can contribute to HF worsening. Unmasking these factors is essential, as specific treatments can markedly improve the patient's clinical status.